Fenton-like nanocatalyst for photodegradation of methylene blue under visible light activated by hybrid green DNSA@Chitosan@MnFe2O4. (1st October 2018) - Shoueir, Kamel; El-Sheshtawy, Hamdy; Misbah, Mohammed; El-Hosainy, Hamza; El-Mehasseb, Ibrahim; El-Kemary, Maged
Graphical abstract: Highlights: DNSA modified CS for the first time and acting as bridge between MB dye and MnFe2 O4 . Excellent thermal stability achieved upon coating with MnFe2 O4 . Hybrid DNSA@CS@MnFe2 O4 exhibited adsorption and potent photodegradation towards MB under visible light with the aid of H2 O2 . Hot filtration test proved the heterogeneity of reaction and good recyclability was attained with DNSA@CS@ MnFe2 O4 . Abstract: High efficient 3, 5-Dinitrosalicylic acid/Chitosan/MnFe2 O4 (DNSA@CS@MnFe2 O4 ) nano photocatalyst was prepared to enrich both adsorption and photodecomposition under visible light. This paper focused on the importance of DNSA@CS as an excellent connector between methylene blue (MB) and MnFe2 O4 for accelerating photodegradation with the encouragement of photo-Fenton catalytic reagent hydrogen peroxide (H2 O2 ). The optimum conditions were: contact time, 30 min, H2 O2 concentration, 0.16 M, pH factor 9 and dosage 0.06 g/l at R.T, allowing excellent catalytic achievements 98.9% degree of decolorization in 30 min. More interestingly, the hybrid DNSA@CS@MnFe2 O4 mechanism explained on the basis of coexistence of Mn 2+ /Mn 3+ and Fe 3+ /Fe 2+ redox couples during the reaction. The photocatalytic decolorization experimentally affirmed the suitability of DNSA@CS@MnFe2 O4 obeying Langmuir-Hinshelwood model. Also, the nano-catalytic system was stable even after five runs. The prepared nanostructured catalyst provides simple fabrication to promote deep understand criteria for the mechanistic role of MnFe2 O4 catalyst for degradation of MB molecules.